2021
DOI: 10.1080/09064702.2021.1891278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of live-body weight and the number of eggs produced for introduced and local chickens in Ethiopia

Abstract: Ethiopia's 60 million chickens are reared primarily in free range, smallholder systems. Therefore, upgrading smallholder poultry to small-scale commercial systems is central to rural development. With the aim of providing access to improved chicken by rural farmers in Ethiopia, the live body weight at week 17 and number of eggs per bird per week for one locally improved and three tropically adapted dual-purpose chicken strains was tested through a project called the African Chicken Genetic Gains. Both traits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Similar genotype by location interaction effect on growth traits has been documented in improved indigenous and tropically adapted chickens ( Ajayi et al, 2020 ; Guni et al, 2021b ). The lower mortality of birds in Nasarawa State might be attributed to better management practices, which is consistent with the findings of Alemu et al (2021) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar genotype by location interaction effect on growth traits has been documented in improved indigenous and tropically adapted chickens ( Ajayi et al, 2020 ; Guni et al, 2021b ). The lower mortality of birds in Nasarawa State might be attributed to better management practices, which is consistent with the findings of Alemu et al (2021) .…”
Section: Discussionsupporting
confidence: 87%
“…In a related study, Sztandarski et al (2021) found associations between weather conditions and performance of birds. Alemu et al (2021) also reported that climate may lead to body weight differences in different strains of improved tropically adapted chickens.…”
Section: Discussionmentioning
confidence: 98%
“…SDMs were used in our study to identify the most relevant environmental predictors influencing habitat suitability for chickens. The environmental predictors identified in the present study (related with elevation, precipitation, soil clay content, solar radiation, and temperature) were reported in earlier studies for their influences on availability of feed, productivity, prevalence of diseases and parasites [ 26 , 46 , 138 , 139 ]. The habitat suitability maps produced by SDMs suggest that the 26 Ethiopian indigenous chicken sample populations may have gone through different environmental selective pressures which give rise to phenotypic and genetic differentiation.…”
Section: Discussionsupporting
confidence: 56%
“…Lozano-Jaramillo A. et al (2019) and Alemu et al (2021) have also observed effects of precipitation and temperature on improved chicken breeds introduced to smallholder farmers in Ethiopia.…”
Section: Discussionmentioning
confidence: 97%
“…The influence of isothermality (Bio3), temperature (Bio4 and Bio11), precipitation (Bio19), solar radiation, and water vapor pressure on trait differentiation may be related with adaptive physiology of chickens, in terms of their biological response to extremes in relative humidity and heat stress. Lozano-Jaramillo A. et al (2019) and Alemu et al (2021) have also observed effects of precipitation and temperature on improved chicken breeds introduced to smallholder farmers in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%